Populist Syndrome and Nonmarket Strategy - Markus, Stanislav; Martínez Suárez, Julio; Blake, Daniel J. (John Wiley and Sons Inc, 2024)
Although recognized as a defining feature of the current political era,populism and its implications for non-market strategy remain undertheorized. We offer a framework that (a) conceptualizes populism and its progression over time; (b) outlines the risks populism generates for firms; and (c) theorizes effective nonmarket strategies under populism. Our framework anchors the political risk profile of populism in three interdependent elements: anti-establishment ideology,de-institutionalization,and short-term policy bias. These elements jointly shape the policymaking dynamics and institutional risks for firms under populism. Our analysis shows how firms can calibrate two nonmarket strategies – political ties and corporate social responsibility – to mitigate populism-related risks. We specify how particular configurations of political ties and CSR activities,aimed at the populist leadership,bureaucrats,political opposition,and societal stakeholders,minimize risk under populism. Further,we theorize how the effectiveness of specific attributes of political ties and CSR – namely their relative covertness (more vs. less concealed) and their relative focus (narrowly vs. widely targeted) – varies as a function of firm type (insiders vs. outsiders) and the probability of populist regime collapse. Finally,we address how motivated reasoning may bias firms' assessments of regime fragility and resulting strategy choices. © 2022 The Authors. Journal of Management Studies published by Society for the Advancement of Management Studies and John Wiley & Sons Ltd.
Keywords: Corporate political activity; Nonmarket strategy; Political institutions; Political risk; Populism; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 16 - Paz, justicia e instituciones sólidas; ODS 17 - Alianzas para lograr los objetivos